Decarbonization and ecomodernization of the economy as a resource-energy-efficient way of post-war reconstruction of Ukraine - Petruk, Vasyl; Polyvyanchuk, Andriy; Petruk, Galina; Hura, Kostyantyn; Faichuk, Volodymyr (Видавництво Львівської політехніки, 2024)
Global climate changes are taking place on our planet, which cause an increase in the average annual temperature of the atmospheric air, and, therefore, rapid melting of glaciers on all continents and an inevitable rise in the level of the world ocean. This, in turn, can lead to “environmental” wars, a brutal struggle for survival resources, and powerful migration processes. At the same time, one of the main reasons for such global changes and processes is the huge amount of emissions of greenhouse gases and soot particles into the surface layer of the atmosphere (troposphere), caused by anthropogenic and man-made activities, outdated energy-intensive technologies that involve the excessive extraction and use of carbon-containing raw materials, their burning and emission into the atmosphere. However, an alternative to this in postwar Ukraine can only be decarbonization and eco-modernization of its economy based, first of all, on renewable energy sources (in particular, the inexhaustible energy of the Sun), resource-saving, closed, recycling, emission-free and other modern innovative environmental protection and energy-efficient technologies. That is, humanity must definitely go on the path of “green” transformation of not only the economy, but also the greening of all other spheres of life (Hura, Petruk, 2021).
Keywords: decarbonization; eco-modernization of the economy; renewable energy sources; climate change; “greenhouse” effect; solar generation